APPLICATION OF THE CONCEPT OF INTEGRATED QUALITY CONTROL AND QUALITY CONTROL AS A BUSINESS FORCE MEETS THE SATISFACTION OF EMPLOYEE SATISFACTION AND CUSTOMER SATISFACTION ORGANIZATION - DR. FX. Suwarto, DR. FX. Suwarto (Management, 2010)
PMT / TQC system is an Objective Based Management (SBM / MBO) plus a Quality Control Circle (QCC / QCC) with mathematical formulations PMT / TQC = MBS / MBO GKM / QCC. Techniques used in decision-making by management model based on objectives / management by objectives does not vary much with Quality Control techniques are always based on the PDCA that span the hierarchy into eight steps, the second difference is the technique used in the MBS model number / scoring and on Quality Control PDCA is used which is based on statistics. The equation is a second technique seeks to improve the productivity of the never ending / continuous. Concepts and conventions generated GKM / QCC is standardization. Keyword : TQC, MBO, QCC